2019
DOI: 10.3934/cpaa.2019032
|View full text |Cite
|
Sign up to set email alerts
|

Continuous data assimilation for the 3D primitive equations of the ocean

Abstract: In this article, we show that the continuous data assimilation algorithm is valid for the 3D primitive equations of the ocean. Namely, the L 2 norm of the assimilated solution converge to that of the reference solution at an exponential rate in time. We also prove the global existence of strong solution to the assimilated system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…Since its inception in [3,4], the AOT algorithm has been the subject of much recent study in both analytical studies [1,5,6,8,9,10,11,13,15,16,21,22,23,24,25,26,27,28,29,31,30,32,34,35,36,37,39,41,44,45,48,49,50,53] and computational studies [2,12,14,18,20,33,38,40,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Since its inception in [3,4], the AOT algorithm has been the subject of much recent study in both analytical studies [1,5,6,8,9,10,11,13,15,16,21,22,23,24,25,26,27,28,29,31,30,32,34,35,36,37,39,41,44,45,48,49,50,53] and computational studies [2,12,14,18,20,33,38,40,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm works in tandem with a data assimilation method proposed in [4,5]. This algorithm, commonly referred to as the Azouani-Olson-Titi (AOT) or Continuous Data Assimilation (CDA) algorithm, has seen much recent work (see, e.g., [1,2,6,7,8,9,13,14,15,19,20,21,22,23,24,25,26,27,30,31,32,33,34,36,39,40,41,42,45,46,47,48,49,50,51,52,57,59,65] and the references therein.) Specifically, [4] considers the 2D Navier-Stokes system, written abstractly in the form The difficulty is that the initial data is unknown; however, it is assumed that the solution can be measured at certain points.…”
Section: Introductionmentioning
confidence: 99%
“…This seemingly minor change had profound impacts, and the authors of [5] were able to prove that using only sparse observations, the CDA algorithm applied to the 2D Navier-Stokes equations converges to the correct solution exponentially fast in time, independent of the choice initial data. This stimulated a large amount of recent research on the CDA algorithm; see, e.g., [3,6,7,10,11,13,17,18,19,20,21,22,27,31,30,35,40,41] and the references therein. The recent paper [15] showed that CDA can be effectively used for weather prediction, showing that it can indeed be a powerful tool on practical large scale problems.…”
mentioning
confidence: 99%